Conspicuous Consumption and Overlapping Generations? - Ronald Wendner (Economics and Econometrics Research Institute (EERI), 2009)
This paper investigates household decisions, and optimal taxation in an overlapping generations model in which individual utility depends on a weighted average of consumption of ones peers — a “keeping up with the Joneses” consumption externality. In contrast to representative agent economies, the consumption externality generally a?ects steady state savings and growth rates. The nature of the externality's impact, however, critically depends on the rate at which labor productivity declines with age. For a (strongly enough) declining labor productivity (or when people gradually retire), the consumption externality lowers the steady state propensity to consume out of total wealth. The opposite holds for a constant labor productivity. The market economy can be decentralized by a (reverse) unfunded social security system if the rate of labor productivity decline is high (low). In contrast to previous results, the optimal steady state capital income tax is zero, in spite of the consumption externality.
Keywords: D91; E21; O40; 330; Consumption externality; labor productivity; gradual retirement; overlapping generations; keeping up with the Joneses; optimal taxation; capital taxation